Delineating molecular mechanisms of inflammation-induced delirium using a novel mouse model - Skelly, Donal (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Delirium is a syndrome of acute and transient confusion with disruption of attention and cognition; it is a common but underdiagnosed neuropsychiatric condition, which is predictive of increased fimctional decline, dementia and mortality. Despite its high incidence and cost, the molecular mechanisms underlying delirium are poorly understood. Prior cognitive impairment is the primary risk factor for delirium and systemic inflammation is a frequent trigger. The objective of the current thesis was to investigate the CNS response to systemic inflammation, particularly where there is underlying neurodegeneration, using a novel animal model of delirium during dementia.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.